ENHANCING THE VALUE OF HEALTH CARE SERVICES AT A REGIONAL LEVEL. Issue 1 (24th October 2016) - Williams, Galina
Abstract : The presence of a quality health care service (HCS) industry in a region can contribute significantly to the attraction of new industries, retain the existing ones, and contribute to the overall social and economic prosperity of the region. However, when conducting an economic impact assessment it is not always clear how the value of the HCS industry can be increased at a regional level. The HCS industry is often one of the largest industries in a region in terms of creating employment and generating income, but unless it creates linkages with other industries, its contribution to the prosperity of the region will be limited. This paper suggests a methodology for economic impact assessment aimed at increasing the benefits of HCS at a regional level. Using a case study of the Fitzroy Statistical Division, a non‐metropolitan region in Queensland, Australia, the regional economic impact is assessed using input–output analysis. In each region, the key sectors need to be encouraged to enhance connections with the HCS industry in order to enhance the value of HCS in the region.